Hubungan Spiritual Quotient dengan Tingkat Stres pada Mahasiswa Kedokteran di Semarang - Irfandi, Nurahmat Yanisa; Widayati, Ratih; Fuad, Wijayanti (Fakultas Kedokteran Universitas Trisakti, 2024)
Background Student medical is one major favorite where his students are confronted with various relative constraints difficult to take, like many it's a mandatory academic target resolved and prosecuted adapt from transition high school to college sure height different from facet academic, then environment social making student stressed and triggered it happened stress. stress will raise problems for students when not managed with ok. The spiritual Quotient (SQ) is one factor that plays a role in controlling stress. Students who have a High Spiritual Quotient will be capable of controlling stress. Methods Research this characteristic quantitative, observational analysis with an approach cross-sectional. The instrument used consists of a questionnaire from the level Spiritual Quotient with the title “questionnaire spiritual intelligence” and level stress with the title